Plant Senescence: a self induced process - Trippi, Victorio Segundo (2009)
This review suggests that plant senescence is a self-induced process. This proposition is based on changing relations among cells and organs in a growing system, originated by growth itself, and differentiation due to adaptation to internal and external environments conditions, which are also changing conditions during development. This succession of events has been called stressfunctions or emerged features. Among them are mentioned: growth in height restricting water supply to the most distal parts; the seed germination, modifying the relations with oxygen during the change from anaerobic metabolisms to an aerobic one; leaf growth and differentiation generating toxic hyperoxic conditions in autotrophic cells; the source-sink relations, inducing senescence in source organs by deficiency; sugar accumulation and growth regulators or hormones inducing oxidative process. The reactive oxygen species (ROS), generated under different stress condition, should be major modulators of growth and differentiation processes that became in senescence of both autotrophic organs, which are more sensitive to oxidative process and heterotrophic ones, which being more tolerant to oxidations assure specie perpetuation.